Benefits of Apixaban over Warfarin are Consistent, Irrespective of TTR - Vinall, Maria (MD Conference Express, 2011)
The results of a subanalysis of data from ARISTOTLE, demonstrated that the benefit of apixaban over warfarin was not related to the quality of INR control at the individual ARISTOTLE study centers.